Fixed-time attitude coordination control for spacecraft with external disturbance. (August 2021) - Zhuang, Minglei; Tan, Liguo; Song, Shenmin
Abstract: This paper studies the fixed-time stability of attitude coordination control for spacecraft formation flying (SFF) in the presence of some external disturbance. Firstly, to ensure that the states converge to the origin within a fixed time, a novel nonsingular terminal sliding mode surface (NTSMS) is designed. The convergence time is bounded by some predefined constants. Secondly, an attitude synchronization controller is proposed based on the designed NTSMS, which guarantees the fixed-time stability of SFF under an undirected communication topology. Finally, a fixed-time adaptive control law is designed for cases in which the boundary of the external disturbance is unknown. The fixed-time stability is guaranteed by a revised form of the proposed NTSMS. Simulation results show that the proposed controllers provide fixed-time stability and outperform existing finite-time controllers. Highlights: Two terminal sliding surfaces are designed to stabilize the system in fixed-time. Designed controllers solve fixed-time attitude tracking synchronization problem well. Designed control schemes have strong robustness against change of initial conditions.